Bilateral vs. Unilateral countermovement jumps: comparing the magnitude and direction of asymmetry in elite academy soccer players - Bishop, C.; Abbott, W.; Brashill, C.; Turner, A.; Lake, J.; Read, P. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were to compare the magnitude and direction of asymmetry in comparable bilateral and unilateral countermovement jumps (CMJs). Forty-five elite academy soccer players from under-23 (n = 15), under-18 (n = 16), and under-16 (n = 14) age groups performed bilateral and unilateral CMJs as part of their routine preseason fitness testing. For the magnitude of asymmetry, no significant differences were evident for any metric between tests. However, the eccentric impulse asymmetry was significantly greater than mean force and concentric impulse in both bilateral and unilateral tests (p < 0.01). For the direction of asymmetry, Kappa coefficients showed poor levels of agreement between test measures for all metrics (mean force = -0.15, concentric impulse = -0.07, and eccentric impulse = -0.13). The mean jump data were also presented relative to the body mass for each group. For the bilateral CMJ, significant differences were evident between groups but showed little consistency in the same group performing better or worse across metrics. For the unilateral CMJ, eccentric impulse was the only metric to show meaningful differences between groups, with the under-18 group performing significantly worse than under-23 and under-16 players. This study highlights that despite the magnitude of asymmetry being similar for each metric between comparable bilateral and unilateral CMJs, consistency in the direction of asymmetry was poor. In essence, if the right limb produced the larger force or impulse during a bilateral CMJ, it was rare for the same limb to perform superior during the unilateral task. Thus, practitioners should be aware that bilateral and unilateral CMJs present different limb dominance characteristics and should not use 1 test to represent the other when measuring between-limb asymmetries.